313Long-acting bronchodilators and risk of acute coronary syndrome. (2nd September 2021) - Parkin, Lianne; Williams, Sheila; Sharples, Katrina; Barson, David; Horsburgh, Simon; Jackson, Rod; Dummer, Jack
Abstract: Background: There is concern that long-acting bronchodilators (long-acting muscarinic antagonists [LAMAs]) and long-acting beta2 -agonists [LABAs]) may further increase the already elevated risk of cardiovascular events in patients with chronic obstructive pulmonary disease (COPD). Guidelines recommend stepwise escalation from one to two long-acting bronchodilators in patients with uncontrolled symptoms, but information about the impact of this treatment intensification on acute coronary syndrome (ACS) risk is limited. Methods: We undertook a nested case-control study using national administrative data to estimate the risk of ACS in users of dual LAMA and LABA therapy, and users of LABA monotherapy, relative to users of LAMA monotherapy. The underlying study cohort comprised patients aged >45 years who initiated long-acting bronchodilator therapy for COPD between 2006 and 2013 (n = 83, 417). Cases were patients diagnosed with fatal or non-fatal ACS after cohort entry (n = 5, 399). Up to 10 controls per case, matched by age, sex, date of cohort entry, and COPD severity, were randomly selected from the study cohort using risk set sampling. Odd ratios and 95% confidence intervals were estimated using conditional logistic regression. Results: Relative to current use of LAMA monotherapy, the adjusted odds ratios for current use of dual LAMA and LABA therapy, and of LABA monotherapy, were 1.28 (95% CI 1.13–1.44) and 1.0 (95% CI 0.91–1.10), respectively. Conclusions: Use of two long-acting bronchodilators rather than LAMA monotherapy, is associated with a higher risk of ACS, while the risks associated with LAMA and LABA monotherapy are comparable. Key messages: The clinical benefit of adding a second long-acting bronchodilator to LAMA or LABA monotherapy is modest and, at the same time, is associated with an increased risk of ACS in a patient group already at high risk.